1998
DOI: 10.1159/000016451
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition and Developmental Defects of Enamel in 2- to 6 -Year-Old Saudi Boys

Abstract: Three hundred and ninety boys aged 2, 4 or 6 years from Riyadh, Saudi Arabia, took part in a survey in 1993/94. The main aims of the study were first, to identify factors related to malnutrition in young children since a study of older children from the same area 1 year before had shown malnutrition to be strongly related to prevalence of developmental defects of enamel (DDE) of permanent teeth and, second, to identify factors related to the prevalence of developmental defects of primary teeth. Enamel defect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0
14

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 29 publications
1
57
0
14
Order By: Relevance
“…9,30,40 Malnutrition may cause enamel hypoplasia, and just like iron deficiency anemia, it may lead to reduced salivary secretion and low buffering capacity. 7,11,24,35,42,43 Childhood malnutrition is still a major problem in Brazil, especially in the North and Northeast regions, 44 which may contribute to a larger number of decayed teeth in these regions. The mean DMFT (number of deciduous teeth that are decayed, extracted or indicated to be extracted and filled) at the age of five years in the North region is approximately 27% higher than the mean for the Southeast region.…”
Section: Susceptible Hostmentioning
confidence: 99%
See 2 more Smart Citations
“…9,30,40 Malnutrition may cause enamel hypoplasia, and just like iron deficiency anemia, it may lead to reduced salivary secretion and low buffering capacity. 7,11,24,35,42,43 Childhood malnutrition is still a major problem in Brazil, especially in the North and Northeast regions, 44 which may contribute to a larger number of decayed teeth in these regions. The mean DMFT (number of deciduous teeth that are decayed, extracted or indicated to be extracted and filled) at the age of five years in the North region is approximately 27% higher than the mean for the Southeast region.…”
Section: Susceptible Hostmentioning
confidence: 99%
“…30,43 In these newborns, enamel defects are associated with gestational diseases, such as maternal infection, metabolic disorders (hypoxemia, nutritional disorders, hypocalcemia) and performance of medical procedures (laryngoscopy and endotracheal intubation). 46 In infants, the presence of infections, metabolic disorders, chemical toxicity and inherited diseases also cause the development of enamel hypoplasia.…”
Section: Susceptible Hostmentioning
confidence: 99%
See 1 more Smart Citation
“…A higher incidence of the enamel defects in the upper incisors than in the lower incisor in both groups was observed in our study. Li Y et al, [16], Rugg-Gunn AJ et al, [17] found relatively similar result. The deviation in the results may be due to the diversity of the methodological procedures and racial differences.…”
Section: Resultsmentioning
confidence: 66%
“…This would overcome the anomaly in the Cochrane Review of, in effect, comparing fluorosis levels recorded in cooler, better nourished populations (such as Newcastle upon Tyne) with those in hot, less-wellnourished populations (such as India, Saudi Arabia and Namibia). Undernutrition is a recognised risk factor for dental enamel defects 32,33 and the severity recorded is substantially different in areas of the world with different levels of development. The rationale for including data from communities with water fluoride concentrations higher than those recommended is unclear, and it is not applicable to the evaluation of water fluoridation where fluoride concentrations are controlled and maintained within acceptable limits.…”
Section: Dental Fluorosismentioning
confidence: 99%